2007
DOI: 10.4049/jimmunol.178.3.1882
|View full text |Cite
|
Sign up to set email alerts
|

Diverse and Potent Chemokine Production by Lung CD11bhigh Dendritic Cells in Homeostasis and in Allergic Lung Inflammation

Abstract: Lung CD11chigh dendritic cells (DC) are comprised of two major phenotypically distinct populations, the CD11bhigh DC and the integrin αEβ7+ DC (CD103+ DC). To examine whether they are functionally distinguishable, global microarray studies and real-time PCR analysis were performed. Significant differences between the two major CD11chigh DC types in chemokine mRNA expression were found. CD11bhigh DC is a major secretory cell type and highly expressed at least 16 chemokine mRNA in the homeostatic state, whereas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
156
2
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 168 publications
(165 citation statements)
references
References 70 publications
5
156
2
2
Order By: Relevance
“…Samples were then treated for a further 5 min with EDTA to disrupt T cell-DC complexes. cDCs were identified as CD11c high , MHC class II high (I-A b ) (17), and pDCs as CD11c int , PDCA-1 ϩ cells (18,19).…”
Section: Recovery Of Leukocytes From Micementioning
confidence: 99%
“…Samples were then treated for a further 5 min with EDTA to disrupt T cell-DC complexes. cDCs were identified as CD11c high , MHC class II high (I-A b ) (17), and pDCs as CD11c int , PDCA-1 ϩ cells (18,19).…”
Section: Recovery Of Leukocytes From Micementioning
confidence: 99%
“…Furthermore, respiratory cDCs are preferentially localized in the lung interstitium, and upon activation, these cells produce a range of inflammatory mediators (26,27). A previous study has demonstrated that the inhalation of pathogenic material, such as bacteria or viral particles, induce a very rapid recruitment of DCs into the airways of rodents, in some cases peaking already 2 h after challenge (28).…”
Section: Losartan Inhibits Lung Cdcs Maturation In Lps-induced Alimentioning
confidence: 99%
“…First, lung CD11b 1 DC massively produce proinflammatory chemokines thus attracting CD4 1 and CD8 1 effector lymphocytes to airways, to mediate effector functions [3]. Legge demonstrated that these CD11b 1 inflammatory DC indeed boost CD8 1 effector activity in the lung [49].…”
Section: Lung DC Subsets and Antiviral Immunity: Influenza As The Parmentioning
confidence: 99%
“…The function of DC during allergen challenge could be the local restimulation of effector function in lung resident lymphocytes, or alternatively could be the recruitment of these effector Th2 cells [60]. In allergen-challenged mice, CD11b 1 DC are a prominent source of the chemokines CCL17 and CCL22, thus recruiting CCR4 1 Th2 cells to the lungs [3,61]. A recent study employing selective depletion of lung CD11b 1 myeloid cells (most likely CD11b 1 inflammatory DC) in CD11b-DTR mice indeed identified these cells, and not bronchial epithelial cells, as the critical source of CCL17 and CCL22 [62].…”
Section: The Role Of Lung DC Subsets In Allergy and Asthmamentioning
confidence: 99%
See 1 more Smart Citation